Lectin-Like Bacteriocins - Maarten G. K. Ghequire; Başak Öztürk; René De Mot (Frontiers in Microbiology, 2018)
Bacteria produce a diverse array of antagonistic compounds to restrict growth of microbial rivals. Contributing to this warfare are bacteriocins: secreted antibacterial peptides, proteins and multi-protein complexes. These compounds typically eliminate competitors closely related to the producer. Lectin-like bacteriocins (LlpAs) constitute a distinct class of such proteins, produced by Pseudomonas as well as some other proteobacterial genera. LlpAs share a common architecture consisting of two B-lectin domains, followed by a short carboxy-terminal extension. Two surface-exposed moieties on susceptible Pseudomonas cells are targeted by the respective lectin modules. The carboxy-terminal domain binds D-rhamnose residues present in the lipopolysaccharide layer, whereas the amino-terminal domain interacts with a polymorphic external loop of the outer-membrane protein insertase BamA, hence determining selectivity. The absence of a toxin-immunity module as found in modular bacteriocins and other polymorphic toxin systems, hints toward a novel mode of killing initiated at the cellular surface, not requiring bacteriocin import. Despite significant progress in understanding the function of LlpAs, outstanding questions include the secretion machinery recruited by lectin-like bacteriocins for their release, as well as a better understanding of the environmental signals initiating their expression.